L’émergence du concept de « violence obstétricale »: l’impact du mouvement féministe - Azcué, Mathieu; Tain, Laurence (Santé Publique, 2022)
La littérature scientifique a exploré de nombreux aspects relatifs à la notion de « violence », mais elle n’a jamais cherché à l’appréhender, à notre connaissance, en termes de généalogie vis-à-vis des mouvements féministes. Il s’avère par ailleurs que la formulation du concept de « violence obstétricale » est récente alors que l’expérience est ancienne. C’est ce paradoxe que cet article interroge. Plus précisément, cette contribution vise à élucider comment les mouvements féministes ont pu jouer un rôle facilitateur dans l’émergence de ce concept dont la généalogie s’ancre dans la réflexivité hospitalière et les mouvements féministes. En se saisissant de l’observation d’une association féministe engagée dans la pratique des accouchements alternatifs, cette étude vise à appréhender comment les dynamiques militantes ont ouvert la voie à ce nouveau concept. La recherche de terrain a permis d’identifier deux postures à partir d’entretiens mené auprès des usagères du système hospitalier. L’analyse de l’histoire de cette association montre que c’est un compromis interne à la rencontre entre ces deux postures qui a favorisé un espace de parole pour les parturientes et des négociations avec l’hôpital local pour des réalisations concrètes. La discussion analyse ces deux postures au prisme des points de vue féministes universaliste et différencialiste, ainsi que de la sociologie du corps. La conclusion interroge cette dynamique des mouvements sociaux, se demandant si on peut y observer un processus analogue.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; approches et analyses; care; corps; cours; discipline; gynécologie; inégalités; médecine; obstétrique; patriarcat; pol4102; premier cycle; périodes historiques; santé; sciences; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; violences

Challenging the “old boys club” in academia: Gender and geographic representation in editorial boards of journals publishing in environmental sciences and public health - Dada, Sara; van Daalen, Kim Robin; Barrios-Ruiz, Alanna; Wu, Kai-Ti; Desjardins, Aidan; Bryce-Alberti, Mayte; Castro-Varela, Alejandra; Khorsand, Parnian; Santamarta Zamorano, Ander; Jung, Laura; Malolos, Grace; Li, Jiaqi; et al. (PLOS Global Public Health, 2022)
In light of global environmental crises and the need for sustainable development, the fields of public health and environmental sciences have become increasingly interrelated. Both fields require interdisciplinary thinking and global solutions, which is largely directed by scientific progress documented in peer-reviewed journals. Journal editors play a critical role in coordinating and shaping what is accepted as scientific knowledge. Previous research has demonstrated a lack of diversity in the gender and geographic representation of editors across scientific disciplines. This study aimed to explore the diversity of journal editorial boards publishing in environmental science and public health. The Clarivate Journal Citation Reports database was used to identify journals classified as Public, Environmental, and Occupational (PEO) Health, Environmental Studies, or Environmental Sciences. Current EB members were identified from each journal’s publicly available website between 1 March and 31 May 2021. Individuals’ names, editorial board roles, institutional affiliations, geographic locations (city, country), and inferred gender were collected. Binomial 95% confidence intervals were calculated for the proportions of interest. Pearson correlations with false discovery rate adjustment were used to assess the correlation between journal-based indicators and editorial board characteristics. Linear regression and logistic regression models were fitted to further assess the relationship between gender presence, low- and middle-income country (LMIC) presence and several journal and editor-based indicators. After identifying 628 unique journals and excluding discontinued or unavailable journals, 615 journal editorial boards were included. In-depth analysis was conducted on 591 journals with complete gender and geographic data for their 27,772 editors. Overall, the majority of editors were men (65.9%), followed by women (32.9%) and non-binary/other gender minorities (0.05%). 75.5% journal editorial boards (n = 446) were composed of a majority of men (>55% men), whilst only 13.2% (n = 78) demonstrated gender parity (between 45–55% women/gender minorities). Journals categorized as PEO Health had the most gender diversity. Furthermore, 84% of editors (n = 23,280) were based in high-income countries and only 2.5% of journals (n = 15) demonstrated economic parity in their editorial boards (between 45–55% editors from LMICs). Geographically, the majority of editors’ institutions were based in the United Nations (UN) Western Europe and Other region (76.9%), with 35.2% of editors (n = 9,761) coming solely from the United States and 8.6% (n = 2,373) solely from the United Kingdom. None of the editors-in-chief and only 27 editors in total were women based in low-income countries. Through the examination of journal editorial boards, this study exposes the glaring lack of diversity in editorial boards in environmental science and public health, explores the power dynamics affecting the creation and dissemination of knowledge, and proposes concrete actions to remedy these structural inequities in order to inform more equitable, just and impactful knowledge creation.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; discipline; discours dominant; intersectionnalité; médecine; projet charge mentale; périodes historiques; racisme; santé; santé publique; sciences; sexisme; systèmes d'oppressions; thématiques

État de lieu des données internationales sur les inégalités de genre dans le développement international - Machkouri, Zora Ait El; Bourassa-Dansereau, Caterine; Langevin, Marie (Cahiers de recherche OFDIG, 2022)
Ce cahier présente un premier état des lieux du développement inclusif par le genre (DIG) et brosse le portrait des sources de données internationales et institutionnelles existantes et accessibles au sujet du développement inclusif afin d’outiller l’Observatoire et de soutenir ses partenaires dans leur volonté de se saisir de cette problématique de l’égalité et de participer concrètement aux défis qui en découlent. En répertoriant les sources de données existantes, en analysant leurs caractéristiques et leurs lacunes ainsi qu’en identifiant les angles morts dans la couverture des dimensions inégalitaires persistantes au sein des secteurs clés du DIG (milieux économiques, systèmes éducatifs, domaine de l’enseignement supérieur et de la recherche ), nous cernons des enjeux qui sont au cœur de la mission de l’Observatoire.
Keywords: 2000 à aujourd'hui; OFDIG; afrique; amériques; approches et analyses; discipline; développement durable; empowerment; féminisme décolonial; genre; identités LGBTQIA2+; inégalités; point de vue situé; périodes historiques; ressource en ligne; régions géographiques; statistiques; systèmes d'oppressions; thématiques

Unlocking the Power of Allyship: Giving Health Care Workers the Tools to Take Action Against Inequities and Racism - Noone, Damien; Robinson, Lisa A.; Niles, Chavon; Narang, Indra (NEJM Catalyst Innovations in Care Delivery, 2022)
Everyone, not just marginalized groups, must fight racism and oppression. Members of privileged groups must learn to be allies. Toronto’s Hospital for Sick Children developed a series of workshops to teach them how.Summary Oppression and racism are pervasive in the health care environment and directly impact patients, physicians, and other health care practitioners. Fostering and promoting allyship skills can increase inclusion in health care and advance systemic change. The Hospital for Sick Children in Toronto developed a foundational allyship workshop to increase awareness and understanding of interpersonal, systemic, and institutional oppression and discrimination in the large pediatric academic center. The workshop emphasizes individual accountability and how to speak up and act against oppression through critical allyship. The authors report promising results around the engagement and desire to practice allyship amongst health care providers.
Keywords: allié·e·s; amériques; approches et analyses; canada; cours; discipline; médecine; ontario; oppression; premier cycle; pédagogie; pédiatrie; racisme; régions géographiques; résistance; santé; sciences; sex2283; systèmes d'oppressions; thématiques; toronto; violences